(untitled) (Economic and Political Thought, 2014)
As a result of the global financial crisis, the European Union countries suffered deep recession. It turned out that the financial system, especially the European banking sector, is not resistant to the influence of such events mainly because of imperfect financial architecture. Undertaken measures aimed at structural reforms and the establishment of a banking union. While structural reforms of the banking sector covered all the European Union countries, the banking union will affect only the Eurozone countries and those remaining ones that express the will to participate in the new financial architecture. It will constitute a good basis for undertaking further strong integration steps in Europe.